Adoption of advanced agro-technologies: A harbinger of enhanced income from Coconut, Arecanut and Cocoa farming - Surekha; Bhavishya; P, Subramanian; Bhat, Ravi; Apshara, S Elain (Indian Horticulture, 2022)
Coconut, arecanut and cocoa are an important plantation crops which are a livelihood option for a substantial number of farm families in India. Farmers could increase their net income significantly by adopting the advanced agrotechnologies. This article provides a glimpse of these technologies that could enhance farm income by reducing the cost involved in the production systems or improving the yield.